The Use of Verbs in Astrophysical Research Paper Abstracts: Sociolinguistic Implications - David Israel Méndez Alcaraz; M. Ángeles Alcaraz (CV. Rustam, 2025)
This study aims to explore the use of verbs in a corpus of research paper abstracts retrieved from four English-written top journals published in astrophysics during 2011-2021. From a diachronic point of view, we notice an overall decrease in the use of the passive voice and fluctuating patterns in the verbal parameters analysed, with no substantial statistically significant differences among them. By contrast, from a cross-journal standpoint, we observe some significant differences in the use of verbs between the journals studied. These discrepancies could be interpreted in terms of distinct sociolinguistic frameworks, as astrophysicists may employ verbal constructions in dissimilar ways depending on whether English is their mother tongue or not. In average, non-native English researchers are likely to create longer abstracts with more purpose and linking clauses, more verbs and variants and also more passive voices, more past and future tenses and fewer modal verbs per number of authors. Conversely, native English writers would use fewer auxiliary verbs and a more direct and assertive language. Further linguistic differences can also be noted within native English astrophysicists, depending on their US-based or British areas of influence as well as on the specific scope of each journal.